[Turning on the lights ; Life in Vienna ; The world according to Pidro [videorecording] - Javier, Danny; Lazaro, Cheche (The Probe Team, 1992)
Discusses electricity failure, the national power plants controversy during the Marcos regime under the new administration of the Department of Energy and National Power Corporation. A story on the lives of Filpino nurses in medical centers of Vienna and Australia. Danny Javier a.k.a. Pidro di Montiverdi has personified the new and true Filipino.